2022
DOI: 10.1021/acsnano.2c07842
|View full text |Cite
|
Sign up to set email alerts
|

Selective Detection and Characterization of Small Cysteine-Containing Peptides with Cluster-Modified Nanopore Sensing

Abstract: It was recently demonstrated that one can monitor ligand-induced structure fluctuations of individual thiolate-capped gold nanoclusters using resistive-pulse nanopore sensing. The magnitude of the fluctuations scales with the size of the capping ligand, and it was later shown one can observe ligand exchange in this nanopore setup. We expand on these results by exploring the different types of current fluctuations associated with peptide ligands attaching to tiopronin-capped gold nanoclusters. We show here that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 68 publications
2
26
0
Order By: Relevance
“…Larger peptides (>10 residues) ejected onto the cluster typically yield a single attachment and long-lived fluctuating states. 27 Figure 2A highlights a typical current trace and corresponding all-points histogram (Figure 2B) of the filtered data (red trace, Figure 2A) from a so-called "low-frequency" peptide (P9C6; see Section 1, Table 1 in the Supporting Information). Numerous attachments of this peptide yield current steps whose magnitude are measured from the peak positions in Figure 2B.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger peptides (>10 residues) ejected onto the cluster typically yield a single attachment and long-lived fluctuating states. 27 Figure 2A highlights a typical current trace and corresponding all-points histogram (Figure 2B) of the filtered data (red trace, Figure 2A) from a so-called "low-frequency" peptide (P9C6; see Section 1, Table 1 in the Supporting Information). Numerous attachments of this peptide yield current steps whose magnitude are measured from the peak positions in Figure 2B.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In this paper, we begin by detecting small cancer marker peptides (<10 residues) and peptides corresponding to proteolytic cleavage products of larger biomarker peptides. These peptides give rise to step-like fluctuations with magnitudes that scale with peptide mass. , This shows promise, but the fact that a single data point results from each current step (i.e., one peptide yields one data point) limits the applicability of cluster enhanced nanopore detection. Therefore, we also report on the detection of larger cancer marker peptides (>12 residues), which give rise to so-called “high-frequency” fluctuations .…”
mentioning
confidence: 99%
“…This was later expanded upon to better understand what physical and chemical properties of peptides give rise to different types of fluctuations upon peptide-cluster linkage. This research found that the presence of a cysteine residue on the peptide was required for its attachment to the nanocluster and that the peptide-cluster interaction resulted in either stepwise current transitions or high-frequency one- or two-state fluctuations, depending on the given peptide (Figure b) . The nature of these current patterns was governed by various factors, such as the peptide’s mass, charge, sequence, length, and configuration.…”
Section: Profiling and Identifying Peptidesmentioning
confidence: 98%
“…This research found that the presence of a cysteine residue on the peptide was required for its attachment to the nanocluster and that the peptide-cluster interaction resulted in either stepwise current transitions or high-frequency one-or two-state fluctuations, depending on the given peptide (Figure 3b). 140 The nature of these current patterns was governed by various factors, such as the peptide's mass, charge, sequence, length, and configuration. Both types of peptide-induced signals could be analyzed to identify the peptides in mixtures.…”
Section: Profiling and Identifying Peptidesmentioning
confidence: 99%
See 1 more Smart Citation